An Efficient Customized Clock Allocation Algorithm for a Class of Timed Automata - Saeedloei, Neda; Kluźniak, Feliks (Anais do Simpósio Brasileiro de Métodos Formais (SBMF), 2022)
We present a new clock allocation algorithm for a fairly general class of timed automata. The algorithm is customized to take advantage of the special properties of automata in this class, and is therefore efficient.